Formal Culture, Practical Sense and the Structures of Fear in Spain - Smith, Gavin (Anthropologica, 2022)
In this article I seek to understand how social memory and fear conjoin at various levels in Spain from the period of the Transition following Franco's death in 1975, to the passing of a Law of Historical Memory in 2007. I argue that the ways in which formal culture in the public sphere interacts with the practical sense of everyday life produces a kind of social regulation appropriate to liberal democracy. I employ two features of Raymond Williams' use of the notion "structure of feeling" to elucidate how this occurs. Formal culture can be understood as the product of a self-conscious program that seeks to produce a coherent "quality of social experience...which gives the sense of a period." By contrast a particular feature of practical sense, that it does "not have to await definition, classification. . .before [it] exert[s] palpable pressure. . .on experience and action" provides the possibility to regulate democratic sovereignty by keeping ordinary people's "dangerous" memories fragmented on the threshold of attaining social definition.